Effect of carbonization temperature on microwave absorbing properties of polyacrylonitrile-based carbon fibers. Issue 11 (2nd November 2017) - Hu, Zhen; Jin, Shuangling; Lu, Wangzhao; Tang, Shan; Guo, Chenting; Lu, Yonggen; Zhang, Rui; Liu, Yan; Jin, Minglin
ABSTRACT: The pre-oxidized fibers were carbonized at the temperature ranging from 400 to 1300 °C for 1 h. The microwave absorption properties of carbon fibers (CFs) were examined in the frequency range of 2–18 GHz. It is found that the reflection loss characteristics are highly sensitive to the carbonization temperature. At a thickness of 2 mm, the CFs obtained at 710 °C exhibit the best microwave absorbing ability with a maximum reflection loss of −22.9 dB at 15 GHz, and a bandwidth exceeding −10 dB in the range 12.4–18 GHz. Results indicate that dielectric loss in cooperation with better matched characteristic impedance results in the excellent microwave absorption of CFs. Low temperature makes ϵ′ and ϵ″ too small to consume the energy of microwave, while over high temperature makes ϵ′ and ϵ″ too large to transmit the microwave into the CFs.